Rebuild the Trust: Predicting the Financial Well-Being of Indonesian Insurers - Astuti, Endang Dwi; Hilman, Muhammad Irfan; Suryajaya, Edbert (Journal of Indonesian Economy and Business, 2025)
Introduction/Main Objectives: The emerging markets’ economic growth relies on stable insurance sectors, which mitigate risk, maintain liquidity, and manage profitability for sustainable growth. This paper aims to examine the financial well-being prediction model using logit regression for Indonesian life and general insurance companies one year and two years before a failure event. Background Problems: The rise of insurance failures erodes people's trust, especially in Indonesia where financial literacy is still an ongoing issue. Novelty: Numerous studies examine the methodology for predicting insurance failure, but some of these procedures have statistical limitations or do not address the unique issue in the emerging markets’ setting. Research Methods: This study employs logistic regression as its methodology and focuses on the life and general insurers operating in Indonesia between 2012 and 2020, using publicly available data. Finding/Results: This study finds the financial well-being of general insurance companies is dependent on their investment performance, profitability, liquidity, change in asset mix, premiums, and surplus growth, leverage, the inflation rate, and change in money reserves. While firm size, the operating margin, premium growth, liquidity change in the asset mix, the combined ratio of loss and expense ratios, surplus growth, and leverage are the key leading indicators of life insurers’ insolvency. Conclusion: Firms with poor investment performance, low premium growth, and extreme levels of leverage are more likely to be insolvent. This study suggests that local authorities should regulate insurance companies' investment strategies, moderate their asset mix changes, and implement sound risk management systems to mitigate performance fluctuations.